Pengaruh Variasi Konsentrasi Polivinil Pirolidon Sebagai Bahan Pengikat Pada Formulasi Tablet Ekstrak Alga Coklat (Sargassum sp.) - Dea Eka Rina (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
The use of brown alga (Sargassum sp.) in pharmaceutical science is used as a form of active substance in a drug. The drug which is made in tablet dosage form consists of brown alga (Sargassum sp.) as the main active substance of the drug and other binding agents consisting of polyvinyl pyrrolidone (PVP). In this study, we will discuss more about the effectiveness of the binder (PVP) in drug preparations using the wet granulation method. To obtain a concentrated extract of brown alga (Sargassum sp.) 96% ethanol was used by the soxhletation method. The manufacture of tablets of brown alga (Sargassum sp.) will be tested with a binder (PVP) in 3 different concentrations, namely, 3%, 5%, and 9%. Before entering the granule printing stage, the drug preparation must pass the evaluation of flow properties, angle of repose, and compressibility. After that, the physical properties of the tablets were evaluated which consisted of weight uniformity, size uniformity, hardness, disintegration time, and half-life. In this study, the results of the evaluation of the physical properties of granules with 3 variations of the formula concentration met the requirements, but in the test of disintegration time, hardness, weight uniformity, and tablet size uniformity, the results showed that the PVP concentrations of 3% and 5% were eligible in drug tablet brown alga